2012
DOI: 10.1016/j.scriptamat.2012.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Atom probe microscopy investigation of Mg site occupancy within δ′ precipitates in an Al–Mg–Li alloy

Abstract: The composition and site-occupancy of Mg within ordered δ' precipitates in a model Al-Mg-Li alloy have been characterized by atom probe microscopy and first-principles simulations. The concentration in the precipitates is found to be almost the same as that of the matrix, however, we show evidence that Mg partitions to the sites normally occupied by Li in the L1 2 structure. Density functional calculations demonstrate that this partition is energetically favorable, in agreement with experimental results.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 34 publications
3
34
0
Order By: Relevance
“…In the SsZ and SpZ, T1 phase fully dissolved into matrix, because the temperature in these regions reached up to 500°C during FSW [22], which was much higher than the solution temperature of T1 phase ($ 220°C) [23]. However, δ′ phase could precipitate at relatively low temperature ($ 100°C) [24] and β′ phase can resist high temperature up to 600°C [25]. Hence, δ′ and β′ phases appeared in all regions of the FSW joint.…”
Section: Microstructural Evolutionmentioning
confidence: 99%
“…In the SsZ and SpZ, T1 phase fully dissolved into matrix, because the temperature in these regions reached up to 500°C during FSW [22], which was much higher than the solution temperature of T1 phase ($ 220°C) [23]. However, δ′ phase could precipitate at relatively low temperature ($ 100°C) [24] and β′ phase can resist high temperature up to 600°C [25]. Hence, δ′ and β′ phases appeared in all regions of the FSW joint.…”
Section: Microstructural Evolutionmentioning
confidence: 99%
“…8a and c), three sets of diffraction spots were found, including Al matrix diffraction spots. The super lattice spots (blue rhombus) were from b 0 (Al 3 Zr) phase or d 0 (Al 3 Li) phase [32,33]. In the BF images ( Fig.…”
Section: Microstructure Of the Fspw 2a97 After Ht1mentioning
confidence: 97%
“…[103] Another limitation is the loss of crystallographic information, strongly dependent on the alloy, and À experimental parameters; in some regions of the reconstruction can lattice planes of certain directions be resolved (pole regions À poles). Although, in special cases, APT can be used to clarify occupancy of elements on sublattices [104,105] or it has been shown that crystallographic arrangement of atoms may be regained altogether. [106,107] www.advancedsciencenews.com www.aem-journal.com…”
Section: Functionalitymentioning
confidence: 99%